The Effect of Sea Fish Powder on Development and Growth of Fetal Teeth Mice (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2023)
Growth and development occur in human teeth, which have experienced growth and development since pregnancy. Teeth are formed from two types of cells: oral epithelial cells, which form the enamel organ, and dental papilla, which produce dentine and pulp. Pregnant women who lack nutrition will impact the growth and development of the fetus, including the teeth. Nutrition is an essential component of dental and oral health. The nutrients needed for dental and oral health are calcium, fluorine, phosphorus, and vitamin D. This study aims to determine the effect of sea fish powder on the development and growth of the fetal toothing parent mice. This research used a true experimental design with a post-test-only control design. Pregnant mice were divided into two groups: the control group, which was given distilled water, and the treatment group, which was given seafish powder. The mouse fetuses were taken at 18 days of gestation, and dentition was observed between the control and treatment groups. Histological preparations of the fetal teeth were observed using hematoxylin-eosin (HE) staining. Fetuses of mice in the treatment group showed tooth development conditions in the early bell stage, while fetuses in the control group showed the initiation stage. There were differences in the growth and development phase of the fetus in mice in the control group and the treatment group given sea fish powder. Providing sea fish powder can accelerate the process of odontogenesis in mouse fetuses.